1991
DOI: 10.1007/bf01437075
|View full text |Cite
|
Sign up to set email alerts
|

Quest for experimental M1 and E1-intercombination transition probabilities in few-electron Xe ions

Abstract: The experimental access to M 1 transition probabilities within the nsanp ~ (1 = Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…-group. Table 2 compares the present intra-L-shell excitation energies with other experimental [9,11,12,[27][28][29] and theoretical [2][3][4][5][6][7][8] results. The comparison is also summarized in figure 5.…”
Section: Excitation Energiesmentioning
confidence: 88%
See 1 more Smart Citation
“…-group. Table 2 compares the present intra-L-shell excitation energies with other experimental [9,11,12,[27][28][29] and theoretical [2][3][4][5][6][7][8] results. The comparison is also summarized in figure 5.…”
Section: Excitation Energiesmentioning
confidence: 88%
“…Year Method 2s 2 1 S 0 2s 2 1 S 0 2s 2 1 S 0 2s 2p 3 P 0 −2s2p 3 P 1 −2s2p 3 P 2 −2s2p 1 P 1 −2p [11] 1992 beam-foil 127.3(3) --Möller et al [27] 1991 beam-foil 126.6(5) --Träbert et al [28] 1990 beam-foil 126.6(5) --Möller et al [29] 1989 beam-foil 126.39(64) -- proper theoretical description of this two-valence-electron system and the associated strong electron-electron interaction. The same holds true for the other excitations.…”
Section: Workmentioning
confidence: 99%
“…The beam-foil study by Möller et al ͓30,31͔ comprised no wavelength calibration effort and instead relied on predicted wavelength values to find the line, and then measured the decay rate of the upper level. Feili et al ͓19͔ also observed the line, but opted not to present it in that publication, because in the stationary calibration light source they had no good reference lines that would frame this particular line.…”
Section: B Be-like Ionsmentioning
confidence: 99%